2019
DOI: 10.1096/fj.201901834r
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐3064‐5p sponged by MALAT1 suppresses angiogenesis in human hepatocellular carcinoma by targeting the FOXA1/CD24/Src pathway

Abstract: Abbreviations: CLSM, confocal laser scanning microscopy; Co-IP, co-immunoprecipitation; FISH, fluorescence in situ hybridization; FOXA1, forkhead box protein A1; HCC, hepatocellular carcinoma; MALAT1, metastasis-associated lung adenocarcinoma transcript 1; MMP12, macrophage metalloelastase; MVD, microvessel density; OS, overall survival; RFS, recurrence-free survival; RIP, RNA binding protein immunoprecipitation; TNM, tumor node metastasis; VEGFA, vascular endothelial growth factor A. AbstractAngiogenesis is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 27 publications
(93 reference statements)
1
34
0
Order By: Relevance
“…MALAT1 acted as a sponge of miRNAs, leading to downregulation of miR-NAs and subsequently abnormal expression of targeted genes. [25][26][27] Here, we made a comprehensive search using the public database miRcode and Starbase, and miR-22-3p was identified to be a target gene of MALAT1, as well as an upstream gene of XIAP in cancer. Therefore, we hypothesized that MALAT1 may compete for miR-22-3p, attenuating the regulatory effect of miR-22-3p on IAPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MALAT1 acted as a sponge of miRNAs, leading to downregulation of miR-NAs and subsequently abnormal expression of targeted genes. [25][26][27] Here, we made a comprehensive search using the public database miRcode and Starbase, and miR-22-3p was identified to be a target gene of MALAT1, as well as an upstream gene of XIAP in cancer. Therefore, we hypothesized that MALAT1 may compete for miR-22-3p, attenuating the regulatory effect of miR-22-3p on IAPs.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 They were demonstrated to act as sponges of miRNAs, leading to the dysregulation of miR-NAs and subsequently the abnormal expression of corresponding target genes. [25][26][27][28] BA has been reported to induce cell death through apoptosis in a variety of cancer cells. 29,30 Nevertheless, the role of autophagy in BA-induced cell death in HCC is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In hepatocellular carcinoma, miR-3064-5p blocked angiogenesis by binding to MALAT1 and regulating the FOXA1 pathway. 26 In GC, circCOL6A3 was found to facilitate tumor progression by acting as a sponge for miR-3064-5p and activating COL6A3. 27 In our research, miR-3064-5p was down-regulated in doxorubicin-resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…A study found that the lncRNA HULC promotes angiogenesis by upregulating SPHK1 in HCC; HULC acts as a ceRNA to increase the expression of transcription factor E2F1 by competitively binding to miR-107 and subsequently results in the activation of the SPHK1 promoter, thus promoting HCC angiogenesis in vivo [ 52 ]. In addition, the lncRNA MALAT1 can promote HCC angiogenesis by sponging miR-3064-5p to activate the forkhead box A1 (FOXA1)/CD24/Src pathway[ 53 ] or by functioning as a miR-140 sponge to enhance vascular endothelial growth factor A expression[ 54 ]. Similarly, LINC00488 , another lncRNA, upregulates the expression of talin 1 to facilitate HCC angiogenesis by sponging miR-330-5p[ 55 ].…”
Section: Role Of Lncrnas As Cernas In Hccmentioning
confidence: 99%